1992
DOI: 10.1055/s-0038-1648513
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Heparin and Prevention of Postoperative Thrombosis in Abdominal Surgery

Abstract: SummaryIn a prospective, double-blind, randomized multicenter trial the efficacy and safety of low molecular weight heparin and unfractionated heparin were compared for the prevention of postoperative deep vein thrombosis in patients undergoing abdominal surgery. Six hundred and seventy-three patients were randomly allocated to the two prophylaxis groups; 20 of these, however, did not undergo surgery and did not receive any prophylaxis. Of the remaining 653 patients 323 received one subcutaneous injection of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 14 publications
(7 reference statements)
1
28
0
1
Order By: Relevance
“…The incidence of PE, bleeding complications, the number and frequency of transfusions, and intraoperative and postoperative blood loss were similar in the two prophylactic groups 12 . Similarly, using a lower dose of fraxiparin of 3000 anti-Xa units once daily in a trial of 653 patients, Koppenhagen et al 13 reported no difference in DVT incidence between LMWH and UFH groups (7·4 versus 7·9 per cent respectively). The lower dose of LMWH was associated with no alteration in bleeding complications.…”
Section: General Abdominal Surgerymentioning
confidence: 95%
See 1 more Smart Citation
“…The incidence of PE, bleeding complications, the number and frequency of transfusions, and intraoperative and postoperative blood loss were similar in the two prophylactic groups 12 . Similarly, using a lower dose of fraxiparin of 3000 anti-Xa units once daily in a trial of 653 patients, Koppenhagen et al 13 reported no difference in DVT incidence between LMWH and UFH groups (7·4 versus 7·9 per cent respectively). The lower dose of LMWH was associated with no alteration in bleeding complications.…”
Section: General Abdominal Surgerymentioning
confidence: 95%
“…Additional data on the efficacy and safety of LMWH was produced by two trials in which the LMWH fraxiparin was compared with UFH 5000 units three times a day 12,13 . In the European Fraxiparin Study Group study, both objectively confirmed DVT (2·8 versus 4·5 per cent; P < 0·050) and proximal DVT (0·4 versus 1·4 per cent; P < 0·050) occurred less frequently in patients receiving LMWH 7500 anti-Xa units once daily than in the UFH group 12 .…”
Section: General Abdominal Surgerymentioning
confidence: 99%
“…It is reported that the use of 3000 IU anti-Xa, 2 h prior to abdominal surgery, eliminates the risk of PTE [7,8]. Even though we adhered to all recommendations for VTE prevention (4000 IU anti-Xa enoxaparin administration and GCS use), and although the patient was initially stratifi ed as being at high risk for PTE, these measures were inadequate to prevent such a serious complication from occurring.…”
Section: Discussionmentioning
confidence: 94%
“…У пациентов отделения интенсив ной терапии на фоне соблюдения превентивных протоколов вероятность развития тромбоза коле блется от 5,5 до 33% (в среднем 12,0%) [48][49][50][51][52][53][54][55][56][57]. У пациентов общехирургического профиля, относя щихся к категории высокого риска, после вмеша тельств на органах брюшной полости и малого таза частота ВТ на фоне изолированного применения одной профилактической методики (эластичной или пневматической компрессии, профилактиче ских доз антикоагулянтов) составляет около 11-13%, а при сочетании нескольких методов уменьша ется до 2% [17,26,27,34,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. При анализе эф фективности отдельных превентивных средств в группе высокого риска можно увидеть следующие цифры: частота развития ВТ на фоне применения стандартных доз гепаринов колеблется от 1,9 до 33%, составляя в среднем 13,4% [18-21, 23, 25, 28, 32-36, 38, 40, 42, 44, 45, 47-57, 59, 60, 62, 64-67, 69-71, 73-82]; на фоне изолированного использо вания эластичной компрессии -от 6 до 26% (сред няя 13,2%) [22,24,27,43,44,46,61,…”
Section: флебология 1 2015unclassified